Learning from Somalia and Ethiopia – the NREN as a Tool for Building National Expertise: A Co-Authorship Between SomaliREN and the World Bank - Firestone, Rachel (My University, 2015)
Countries in the process of developing their ICT ecosystem often face the challenge of end users lacking the skills and information necessary for using the new technological service to its full capacity. States recovering from conflict and emerging out of long periods of isolation tend to experience this imbalance in infrastructure and soft-skill development even more poignantly as they work to expand many services and sectors concurrently. Somalia is a good example of this as its national technical capacity is too nascent to deploy national Research and Education (NREN) infrastructure without importing external expertise. Yet past development experience in-country also demonstrates that reliance on outside expertise can underemphasize local knowledge development and result in institution ill prepared to avail of the technology at their disposal at development project completion. This paper takes a comparative analysis of NREN and education-based technology project experiences in Somalia and Ethiopia aims to explore how an NREN can not only avoid this pitfall, but how the unique services it can provide in addition to connectivity can act as a tool to building out the technical skillsets necessary to support a vibrant ICT sector and competitive developments in the STEM professions across the board.
Keywords: National Research and Education Networks; Human Resource Capacity; Local Content Development; Fragility and Conflict; ICT infrastructure; Economic growth